Transcranial Sonography in Parkinson's Disease and Parkinsonism - Durmaz, Seyma Eroglu; Kursun, Oguzhan; Oztekin, Nese; Karadag, Yesim Sucullu (Neurological sciences and neurophysiology, 2023)
ABSTRACT Background: Transcranial sonography (TCS) is a noninvasive imaging method that practices ultrasound waves to examine the brain structure changes in many neurological pathologies, including Parkinson's disease (PD) and parkinsonism. It allows for the visualization of the substantia nigra (SN), which is affected in these conditions and other brain parts. This technique has shown promise in aiding the diagnosis, follow-up, and progress of PD, in addition to differentiating it from other movement disorders. Our research explores the reliability of TCS in the diagnosis of PD and its impact on the differential diagnosis of atypical parkinsonism syndromes. Subjects and Methods: This study involved 52 PD patients, nine with other parkinsonism, and 54 healthy people. The same neurosonologist, blind to the patient's diagnosis, assessed each individual's SN, and the hyperechogenic area measurement was obtained. These measurements were compared between PD patients, with other forms of PD, and healthy people. In addition, hyperechogenic regions were compared based on the PD subtypes, dominant disease side, severity, and duration of the disease. Results: PD patients were presented with the highest value of SN hyperechogenic regions. TCS had an 87.5% specificity and a 73.3% sensitivity rate for the diagnosis of PD. The akinetic-rigid subtype of PD showed higher hyperechogenicity. In PD patients, there was no correlation between the disease side, length of the disease, Hoehn and Yahr stage, and SN hyperechogenicity. Conclusion: The results of this research demonstrate that the visualizing of SN hyperechogenicity with TCS in PD has diagnostic significance and may be valuable in the differential diagnosis of atypical parkinsonism disorders. However, the evaluation of only the SN may not be sufficient to advantage from TCS in the diagnosis of other parkinsonisms, and it may be essential to investigate the mesencephalon, other basal ganglia, and the third ventricle.